Implementation of Accreditation Management At Madrasah Aliyah Negeri 2 Sumedang - Sariah, Dedeh (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
This research is motivated by the inadequate accreditation preparation time as the main cause of the madrasah unpreparedness in the accreditation assessment process. The head of the madrasah needs to provide special time for teachers and staff to take care of the required documents. In addition, the head of the madrasah must always be ready with information regarding summonses and notifications from the Agency, as well as changes in the accreditation assessment schedule. . This study aims to find out the accreditation management of MAN 2 Sumedang which includes the planning, implementation and evaluation of accreditation. This research uses a qualitative method. This research is located at MAN 2 Sumedang, a flagship madrasah with an accreditation status of